THE EFFECT OF THE IMPLEMENTATION OF APPARATUS RESOURCES ON SERVICE PERFORMANCE AT THE BOGOR REGENCY LAND OFFICE, WEST JAVA PROVINCE - Agustyarsyah Agustyarsyah (International Journal Labs, 2023)
This study aims to analyze how much influence apparatus resources have on service performance at the Bogor Regency Land Office. The location of this research is the Land Office of Bogor Regency, West Java Province. The research design used in this study is a quantitative research approach with explanatory research methods. The research sample used a stratified proportional random sampling technique with a population of 714 and a sample of 233 people determined by the Slovin formula. Data collection techniques in this study used interviews, observation, documentation, and questionnaires. The data analysis method used in this study is determination analysis and linear regression analysis. The hypothesis proves that the implementation of apparatus resources has a significant influence on service performance at the Land Office of Bogor Regency. Based on the results of the study it was concluded that there was an influence of apparatus resources on service performance at the Bogor Regency Land Office 56.5%, where Apparatus Resources, making the Bogor Regency Land Office need efforts in the recruitment process encouragement, self-development abilities and having intellectual ability in increasing their competence very play a role in doing the work and the results achieved from doing the work, about what to do and how to do it, and has a strong relationship with the strategic goals of the organization